Redescription of the deep-sea octopod Benthoctopus normani (Massy 1907) and a description of a new species from the Northeast Atlantic - Allcock, Louise; Strugnell, Jan; Ruggiero, H.; Collins, Martin (2006)
A long-synonymized species Benthoctopus normani (Massy 1907) (Cephalopoda: Octopodidae) is redescribed from material collected over 30 years by the National Oceanography Centre, Southampton and the National Museums of Scotland. It can be distinguished from other octopodid specimens found in deep waters of the Northeast Atlantic by its biserial suckers, lack of ink sac, and simple ligula, which lacks transverse ridges. Examination of the collections led to the identification of a new species of Benthoctopus from the Northeast Atlantic, which is described herein.